Trial by Social Media: An Analysis of Human Rights Violations and Injustice in The Phenomenon of Public Trials - Linda Novianti; Raudlatul Muhasanah (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Advances in information technology have propelled social media into a dominant space in the formation of public opinion, including in responses to legal cases. This situation has given rise to the phenomenon of ‘trial by social media’, namely the practice of public judgement against individuals prior to a final and binding court ruling. This study aims to examine the implications of this phenomenon for the protection of human rights and the principle of justice. This research is situated within a normative legal framework, employing a descriptive-analytical qualitative approach through a literature review. The analysis examines legal norms, legal principles, and relevant academic literature concerning the issues of freedom of expression, the protection of individual rights, and due process of law. Research findings indicate that trial by social media has the potential to violate the principle of the presumption of innocence, the right to privacy, and the right to dignity and reputation. Furthermore, this phenomenon contributes to an increase in digital bullying, the dissemination of personal data, and social stigma with long-term consequences. From a justice perspective, public opinion pressure on social media has the potential to influence the independence and objectivity of law enforcement, thereby creating tension between procedural justice and social expectations. These findings confirm a shift from normative legal authority towards socially constructed legitimacy in the digital sphere. Therefore, there is a need to strengthen regulations, improve digital literacy, and ensure consistent law enforcement to maintain a balance between freedom of expression and the protection of human rights. [Perkembangan teknologi informasi telah mendorong media sosial menjadi ruang dominan dalam pembentukan opini publik, termasuk dalam merespons perkara hukum. Kondisi ini melahirkan fenomena trial by social media, yaitu praktik penghakiman publik terhadap individu sebelum adanya putusan pengadilan yang berkekuatan hukum tetap. Penelitian ini bertujuan untuk mengkaji implikasi fenomena tersebut terhadap perlindungan hak asasi manusia dan prinsip keadilan. Penelitian ini diposisikan dalam kerangka yuridis normatif dengan menggunakan pendekatan kualitatif deskriptif-analitis melalui studi kepustakaan. Analisis dilakukan terhadap norma hukum, asas-asas hukum, serta literatur ilmiah yang relevan dengan isu kebebasan berekspresi, perlindungan hak individu, dan due process of law. Hasil penelitian menunjukkan bahwa trial by social media berpotensi melanggar asas praduga tak bersalah, hak atas privasi, serta hak atas kehormatan dan nama baik. Selain itu, fenomena ini turut mendorong meningkatnya praktik perundungan digital, penyebaran data pribadi, dan stigma sosial yang berdampak jangka panjang. Dari perspektif keadilan, tekanan opini publik di media sosial berpotensi memengaruhi independensi dan objektivitas penegakan hukum, sehingga menimbulkan ketegangan antara keadilan prosedural dan ekspektasi sosial. Temuan ini menegaskan adanya pergeseran dari otoritas hukum normatif menuju legitimasi yang dibentuk secara sosial di ruang digital. Oleh karena itu, diperlukan penguatan regulasi, peningkatan literasi digital, serta konsistensi penegakan hukum guna menjaga keseimbangan antara kebebasan berekspresi dan perlindungan hak asasi manusia.]